Based substrates of sewage sludge for the production of seedlings of Acacia mangium Wild. - Caldeira, Marcos Vinicius Winckler; Favalessa, Marcilene; Gonçalves, Elzimar de Oliveira; Delarmelina, William Macedo; Santos, Fernando Elair Vieira; Viera, Márcio (Comunicata Scientiae, 2014)
The aim of this study was to test the use of sewage sludge as substrate with different components inthe production of seedlings of Acacia mangium. The study was conducted in the Nursery Departmentof Forest Science and Wood Center for Agricultural Sciences, Federal University of Espírito Santo-UFES, Alegre. The treatments consisted of sewage sludge (LE) associated with rice husk in natura(CA), vermiculite (RED) and the organic compound (CO), and treatment with 100% sewage sludge(LE) and substrate commercial (SC).The use of rice husk in natura provides low average for thetraits evaluated and commercial substrate yielded the lowest average for all traits. The use ofvermiculite provided intermediate averages for the traits evaluated. It was found that treatmentswith sewage sludge associated with the organic compound, were those who stood out in front ofthe morphological characteristics evaluated, and the use of 40% CO + 60% CO best suited for theproduction of seedlings of the species.